HUBUNGAN TINGKAT PENGETAHUAN, SIKAP DAN KEPEMILIKAN JAMBAN DENGAN KEBIASAAN BUANG AIR BESAR SEMBARANGAN (BABS) DIDUSUN REJOSARI DESA SERUT KECAMATAN GEDANGSARI KABUPATEN GUNUNG KIDUL - Ahmad Faizal Rangkuti; Dynnia Anindilla Rizkie (Universitas Ahmad Dahlan, 2022)
Open defecation free (ODF) is a dangerous activity both for oneself and the community.Toilet ownership is one indicator of a clean and healthy life behavior program. Open defecation free can be influenced by factors such as the level of knowledge, attitudes, and ownership of latrines.The purpose of this study was to determine the relationship between the level of knowledge, attitudes and ownership of latrines with open defecation (ODF) in Rejosari, Serut, Gedangsari, Gunung Kidul. Research methods used cross-sectional designs. Technique sampling used a cluster random sampling. Total samples were 82 households. Data analysis used chi square test. Based on the results of the univariate test, 18 respondents (22%) had a lack of level of knowledge, 64 respondents (78%) had a good level of knowledge. Not a good attitude as many as 15 respondents (18.3%) and who have a good attitude as many as 67 respondents (81.7%). Respondents who did not have a toilet were 14 respondents (17.1%) and those who had a toilet were 68 respondents (82.9%). Defecation habits are not good as many as 39 respondents (47.6%) and those who have good bowel habits are 43 respondents (52.4%). Bivariate analysis found the value of RP = 2.222 (95% CI: 1.523-3.224) and the value of p <0.05, the value (p = 0.002) for the level of knowledge. RP = 1,985 (95% CI: 1,350, -2,920) and p value <0.05, value (p = 0.013) for attitude. Rp. 2,159 (95% CI: 1,502-3,102) and p value <0.05, value (p = 0.004) for latrine ownership. There was a relationship between the level of knowledge, attitude and ownership of latrines with open defecation habits (ODF).